Объяснение:
a=12
b=-7
c=1
D=[tex](b)^{2} -4ac=(-7)^{2}-4*12*1= 49-48=1[/tex]
[tex]x_{1}=\frac{b+D}{2a}=\frac{7+1}{12*2}=\frac{1}{3}[/tex]
[tex]x_{2}=\frac{7-1}{24}=\frac{1}{4}[/tex]
числа [tex]\frac{1}{4} и \frac{1}{3}[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Объяснение:
a=12
b=-7
c=1
D=[tex](b)^{2} -4ac=(-7)^{2}-4*12*1= 49-48=1[/tex]
[tex]x_{1}=\frac{b+D}{2a}=\frac{7+1}{12*2}=\frac{1}{3}[/tex]
[tex]x_{2}=\frac{7-1}{24}=\frac{1}{4}[/tex]
числа [tex]\frac{1}{4} и \frac{1}{3}[/tex]